Grounded Theory Analysis of High School Students' Content Needs and Wants on the Bakrie University Management Study Program Instagram @manajemen.bakrie - Zahwa Nursyahda; Jerry Heikal (Dinasti International Journal of Digital Business Management, 2024)
Instagram is a social media that aims to help its users share photos with other users. Many universities already have Instagram accounts. The Bakrie University Management Study Program has an Instagram account, namely @manajemen.bakrie, which is used to build interaction with prospective students who are high school students. To build this interaction, you first need to know what kind of content high school students need and want. This research uses qualitative methods with a Grounded Theory Analysis approach. Based on the analysis carried out in this research, there are 3 themes and 9 content categories that high school students need and want. The themes obtained from the results of the coding analysis are Quality, Cost, and Delivery. The categories obtained from the results of the coding analysis are Motivation, Education, Campus, Price, Scholarship, Competition, Activity, Entertainment, and entrance. This analysis found that the highest frequency of themes was in the Quality themes, and the highest category frequency was in the Quality themes in the Campus category.